Estudo de catalisadores bimetálicos de platina ou paládio e cobre suportados em céria para a reação de PROX-CO - Almeida, Janete Cavalcante (2016)
In the present work, catalysts were prepared xCuO / CeO2 (x = 1.0 and 3.0% by mass) doped with Pt or Pd for application in the preferred oxidation reaction of carbon monoxide, also known as PROX-CO reaction. The catalysts, previously activated, were tested in the PROX-CO reaction at low temperature (100-300° C). The syntheses of the catalysts were performed by coprecipitation and the addition of the Pt and Pd promoters by wet impregnation. The catalysts were characterized by thermogravimetric analysis (ATG / ATD), X-ray diffraction (XRD), X-ray fluorescence (FRX), fissestion analysis N2 (BET method), programmed temperature reduction (RTPH2), desorption at programmed temperature of carbon monoxide (DTP-CO), metal dispersion, Fourier transform infrared spectrometry (DRIFTS), X-ray photoelectron spectroscopy (XPS) and transmission electron microscopy (TEM). The products formed during the reaction were analyzed by gas chromatography. The XRD results of these samples showed only peaks characteristic of CeO2. The metal dispersions were shown to be similar as copper loading increased. The spectra of DRIFTS proved the interaction between the CO/metal and as well as the XPS analysis the oxidation state. Different behaviors were observed in bimetallic catalysts. From the results obtained, it was observed that the catalyst 1.0Pt1.0CuO / CeO2 resulted in a material with a greater surface area or specific area than the other catalysts and it showed a good catalytic performance with 99% conversion at a temperature of 100 °C.